2006
DOI: 10.1016/j.ygeno.2005.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Association of single-nucleotide polymorphisms in the suppressor of cytokine signaling 2 (SOCS2) gene with type 2 diabetes in the Japanese

Abstract: Several previous linkage scans in type 2 diabetes (T2D) families indicated a putative susceptibility locus on chromosome 12q15-q22, while the underlying gene for T2D has not yet been identified. We performed a region-wide association analysis on 12q15-q22, using a dense set of >500 single-nucleotide polymorphisms (SNPs), in 1492 unrelated Japanese individuals enrolled in this study. We identified an association between T2D and a haplotype block spanning 13.6 kb of genomic DNA that includes the entire SOCS2 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 57 publications
3
25
0
Order By: Relevance
“…Finally, there was no significant difference in PRKCH genotype distribution between our controls and a group of Japanese individuals from the same geographic area who had type 2 DM (n ϭ 711), from whom samples were collected for a different genetic association study (ref. 30 and Takata Y: unpublished observations). The mean Ϯ SD age of the type 2 DM group was 62.6 Ϯ 11.4 years, which was not significantly different from that of RA patients in this study.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Finally, there was no significant difference in PRKCH genotype distribution between our controls and a group of Japanese individuals from the same geographic area who had type 2 DM (n ϭ 711), from whom samples were collected for a different genetic association study (ref. 30 and Takata Y: unpublished observations). The mean Ϯ SD age of the type 2 DM group was 62.6 Ϯ 11.4 years, which was not significantly different from that of RA patients in this study.…”
Section: Discussionmentioning
confidence: 75%
“…For this study, we selected gene-based SNPs, also referred to as gene-centric evenly spaced common SNPs (27,30), using the following criteria: suitability for designing high-throughput TaqMan SNP genotyping assays; mapping to the gene-centric region, which we assigned to an interval between 10 kb upstream from the transcription start site and 10 kb downstream from the final exon; an average distance of 10 kb between adjacent SNPs whenever possible; and common SNPs with a minor allele Two-stage association study. For the SNP association study, we applied a 2-stage case-control analysis strategy in 1,900 subjects by randomly assigning them to 2 independent subsets.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, SOCS1 or SOCS3 over expression significantly increased plasma insulin levels and perturbed the glucose-lowering effect in insulin tolerance tests. Interestingly, a polymorphism in the non-coding 5' region of the SOCS2 gene is associated with type II diabetes in a Japanese patient population [99]. Whether these effects are related with defects in insulin receptor signaling or insulin secretion remain to be established.…”
Section: Socs Proteins In Rtk Regulated Diseasesmentioning
confidence: 99%
“…To date, little is known about the impact of SOCS2 on pancreatic physiology. However, it has been recently shown that SOCS2 single nucleotide polymorphisms (SNPs) can be associated with type 2 diabetes [27]. Moreover, the authors found that constitutive production of SOCS2 in MIN6 beta cells reduces glucose-stimulated insulin secretion.…”
Section: Introductionmentioning
confidence: 99%